Romanian Journal of Marine, Earth and Environmental Sciences - Geo-Eco-Marina at its 30th issue (Geo-Eco-Marina, 2024)
Romania benefits from a particularly favourable geographical position, being riparian of the Black Sea and at the same time of the main river in the European Union – the Danube, which flows on the country territory for more than 1000 km.Thus, Romania plays the role of an international node of economic, social and cultural relations between East and West, between Asia and Europe, ensuring the connection of the continental and maritime waterways between the Black and North seas and, at the same time, having access to natural resources in the region.